MANAJEMEN WAKTU: KAJIAN HIKMAH RAMADHAN DAN APLIKASINYA DALAM MANAJEMEN MODERNAbbas Muhammad Basalamah - Abbas Muhammad Basalamah (Universitas Nasional, 2017)
The paper is a normative account of ethics in time management as the by-product of doing the fasting in Ramadhan, the ninth month of Islamic year. It the writer’s assumption that the deeper the degree of motivation in devouting oneself the the will of Allah, the better quality of his/her deeds in rituals will be, and the better the implication will be in his capability in time management he/she benefits from the religious faith. Method used is discourse analysis of the Quran ad the Hadits within normative level. The finding of the study reveals that there is a positive correlation between high motivation in performing the Ramadhan fasting with that of time management.